Evaluation of Antimicrobial Activity of Conyza bonariensis Leaf Extracts against Clinically Isolated Fungi Causing Superficial Infection - Yidnekachew Girma; Tamene Milkessa Jiru (Journal of Chemistry)
Plants have been used since long time ago to treat infectious diseases and are considered as important sources of new antimicrobial agents. In this study, crude extracts from leaves of Conyza bonariensis were prepared using methanol, ethyl acetate, hexane, and chloroform. Antimicrobial activity of the extracts was evaluated against pathogenic fungi causing superficial infection (Candida albicans, Malassezia globosa, and Malassezia furfur). Results demonstrated that all extracts had different effects against all the tested fungi with the exception of crude extract using hexane which did not show any effect against M. furfur. A strong effect was observed with chloroform and hexane extracts on C. albicans (32.60 ± 4.69 mm and 27.00 ± 1.00 mm), respectively. While, ethyl acetate and methanol extracts showed the best effect against M. furfur (30.80 ± 1.71 mm and 27.00 ± 1.00 mm), respectively. Moreover, the ethyl acetate showed a considerable effect on M. globosa (25.03 ± 1.05 mm). Minimum inhibitory concentration (MIC) of the fractions was also determined by the microbroth dilution method. The results recorded as the MIC values of the tested extracts against fungi varied from 0.19 ± 0.00 to 66.66 ± 2.86 mg/mL. Ethyl acetate was the best and powerful extract with the lowest MIC value of 0.190.19 ± 0.00 mg/mL for all tested fungi followed by chloroform and methanol extracts with the MIC values ranging from 0.19 ± 0.00 to 0.78 ± 0.00 mg/mL and 0.84 ± 0.68 to 1.56 mg/mL, respectively. Concerning minimum bactericidal concentration (MFC), ethyl acetate was the most potent extract with a MFC value of 0.190.19 ± 0.00 mg/mL for C. albicans and M. furfur. Higher (0.39 mg/mL) MFC was recorded against M. globosa by this extract. In conclusion, solvent extracts of some C. bonariensis can be used to treat infections with pathogenic fungi such as C. albicans, M. furfur, and M. globosa. Further studies should consider this plant as one of the best candidates for the discovery of potent antimicrobial compounds that treat superficial infections.